Cutting Tool Life when Tapping Nickel Based Super Alloy - Dana, Milan; Zetek, Miroslav; Schornik, Vaclav (Manufacturing Technology Journal, 2017)
This work deals with the issue of tapping Inconel 718 alloy. This material is known for its unique properties of high strength at high temperatures, corrosion resistance, high hardness, work hardening and low thermal conductivity. The machinability of Inconel 718 is very hard and cutting tool wear is high.This paper deals with creating internal threads by using monoliths taps. The taps are made of powder metallurgy high speed steel.The taps were provided with coating. Preparation of the hole for the thread has a huge impact on the cutting tool life. If the preparation is poor the inner face of the hole will be work hardened. This makes the cutting tool life far shorter. For the test, taps with different threads per chamfer were used. The second part of the paper is focused on the experiment where cutting tool life was monitored.
Keywords: Thread; Cutting tool life; Tool wear; Inconel 718